Prospective analysis of diagnosis of women with mastalgia - Kalbande, Shubham S.; Ramesh, K. H.; Bahiramwar, Shivani V.; Chollangi, Tarun; Akther, M. D. Jawed (International Surgery Journal, 2024)
Background: Mastalgia is a common condition in women who present to the breast clinics or to the family doctors. It is a chronic problem that affects physical and social activity, work-school activities and sexual activity, and can last years. Therefore, the present study was conducted to determine the aetiology and diagnosis of patients presenting with mastalgia. Methods: This was a hospital based prospective observational study. Total 80 women in reproductive age group who had symptom of mastalgia alone coming to department of general surgery, were taken as study subjects. Demographic, physical and disease characteristics along with ultrasonography (USG) and mammography imaging results analyzed. Results: In present study the average age of patients in our study was 30.93±5.44 years and the mean body mass index (BMI) was of 23.79±2.92. Among cases 20% had complains of irregular menses, 77.5% had breastfed in past and 27.5% cases had history of benign breast diseases. Among cases 57.5% cases had non-cyclical breast pain, 42.5% cyclical breast pain and 58, 72.5% had unilateral breast pain. 53.17% had mild and 10% breast pain severe pain. As per the clinical findings, 32.5% cases were diagnosed with nodularity and 6.5% abscess. Sonography findings were in agreement with the clinical findings. Conclusions: Mastalgia is one of the common symptom in females presenting to breast clinic. Benign breast disorders were commonly associated with mastalgia. Thus, it is very essential to diagnose the risk factors and underlying pathology in mastalgia cases by early diagnosis and prompt treatment of cases.